Orientasi dan Tujuan Kepemimpinan Transformasional dalam Meningkatkan Mutu Pendidikan Islam - Zakki, Mohammad; Maunah, Binti; Patoni, Achmad (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2023)
Leadership orientation is a behavior designed professionally by a leader to achieve Islamic education goals. Employee-oriented leadership behavior is a leadership behavior that focuses on human needs as subordinates. Research uses library research with the aim of sharpening the meaning, orientation and goals of implementing transformational leadership. The data collection technique is by comparing the literature review and the results of previous research, then content analysis is carried out. The results of this study are: Transformational leadership can encourage subordinates to have positive interactions and avoid conflicts, solve problems well because they are interactive and transparent, and leaders are positioned as educators and mentors who are inspiring and innovative, leadership that can create quality islamic education.